Electrochemical studies on zirconium phosphoborate based heterogeneous membranes - Sandeep Kaushal; Pritpal Singh; Susheel K. Mittal (Journal of Electrochemical Science and Engineering, 2014)
Electrode potential measurements have been applied to study electrical characteristics like transport numbers, permselectivity & fixed charged density of zirconium phosphoborate ion exchange membranes. The potential measurements were made across the cation exchange membrane maintained at 27±0.1 °C, using halide and nitrate salts of alkali and alkaline earth metals as electrolytes. The membrane potentials, transport numbers and permselectivity values increase with increase in average concentration from 0.0055 M to 0.0495 M for 1:1 and 1:2 electrolytes. With the increase in concentration of the electrolyte, the number of counter ions interacting with the membrane surface increases leading to enhanced Donnan exclusion responsible for the increase of transport numbers. Fixed charge density of the membrane (X) for 1:2 electrolytes is higher in magnitude than for 1:1 electrolytes indicating that the cation exchange is taking place as hydrated species. This hypothesis is supported by higher transport numbers for alkaline earth metal ions than alkali metal ions throughout the range of concentration.